2020
DOI: 10.1002/jev2.12034
|View full text |Cite
|
Sign up to set email alerts
|

An intact membrane is essential for small extracellular vesicle‐induced modulation of α‐synuclein fibrillization

Abstract: The misfolding and fibrillization of the protein, α‐synuclein (αsyn), is associated with neurodegenerative disorders referred to as the synucleinopathies. Understanding the mechanisms of αsyn misfolding is an important area of interest given that αsyn misfolding contributes to disease pathogenesis. While many studies report the ability of synthetic lipid membranes to modulate αsyn folding, there is little data pertaining to the mechanism(s) of this interaction. αSyn has previously been shown to associate with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 58 publications
0
5
0
Order By: Relevance
“…Our results with EV using protein aggregation assay also strongly implicate alpha-synuclein fibrillisation upon EV membrane binding. Intact EV membranes are essential for the process of EV-mediated aggregation of alpha-synuclein [89]. It is unclear if this effect is exerted by membrane lipids, membrane curvature, membrane-associated proteins, or other factors such as those identified in this study.…”
Section: Discussionmentioning
confidence: 79%
“…Our results with EV using protein aggregation assay also strongly implicate alpha-synuclein fibrillisation upon EV membrane binding. Intact EV membranes are essential for the process of EV-mediated aggregation of alpha-synuclein [89]. It is unclear if this effect is exerted by membrane lipids, membrane curvature, membrane-associated proteins, or other factors such as those identified in this study.…”
Section: Discussionmentioning
confidence: 79%
“…Hill's group has shown that small EVs can accelerate the misfolding of ɑ‐synuclein and promote the production of higher‐order, neurotoxic species. They confirmed that an intact EV membrane is important to support and enhance ɑ‐synuclein misfolding 62,63 . Hill also discussed the potential of EVs as diagnostic biomarkers for neurodegenerative diseases.…”
Section: Evs In the Nervous Systemmentioning
confidence: 85%
“…They confirmed that an intact EV membrane is important to support and enhance ɑ-synuclein misfolding. 62,63 Hill also discussed the potential of EVs as diagnostic biomarkers for neurodegenerative diseases. His lab has identified a panel of nine miRNAs that are dysregulated in exosomes from prion-infected neuronal cells in mice.…”
Section: Evs As Pathologic Entities and Diagnostic Biomarkers In Neur...mentioning
confidence: 99%
“…The EV morphology was evaluated using transmission electron microscopy (TEM) (JEM-1400, Japan), as previously described ( 26 ). The particle size distribution and EV concentrations were measured by nanoparticle tracking analysis (NTA) ( 27 29 ).…”
Section: Methodsmentioning
confidence: 99%